Peran Kepala Sekolah dalam Mengembangkan Budaya Islami di SMK Kesehatan Parigi - Muhammad Rifqi Al-as'ari (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
The principal is a leader in a formal institution that has a very important role in improving the quality of education because the principal must be able to understand, overcome, and correct deficiencies that occur in the school environment as a whole. SMK Kesehatan Parigi is a private school with an Islamic character. The Islamic culture applied at SMK Kesehatan Parigi includes dhuha prayer and reading the Qur'an in the morning, dhuhur prayer in congregation in the afternoon, and muhadhoroh. Successful principal leadership depends on their ability to fulfill their duties as the person assigned to lead the school and their understanding of the school as a complex and distinct entity. School culture influences how group members act and behave, and determines how any problems in the school should be handled by its members. Islamic culture manifests in several forms at the behavioral level, such as the habit of praying in congregation, giving alms, studying hard, and other commendable actions in accordance with Islamic principles. The type of research used in this research is qualitative research, which is a method that produces data from written or spoken words from people and observed behavior. Research subjects are people who will become media in research to obtain the data needed in research.  SMK Kesehatan Parigi is an educational institution with Islamic characteristics, so that many Islamic subjects, such as teaching the Qur'an, Arabic, and worship habits are taught formally in class. In the role of leader, the school principal influences other people (teachers and staff) to work together to achieve a common vision and goal. Strong personality. The ability to provide great, open, and professional services, understand the conditions of the school community. as for the kendaIa faced by the school principal in developing a culture of isIami such as kendaIa that always occurs is the lack of attention of some teachers in providing direction to students who commit mistakes. There is also a problem caused by students, namely the lack of awareness in enforcing existing regulations.